Exploring the Link Between Students’ Sense of School Belonging and Shared Leadership in U.S. High Schools - Sung Tae Jang; Moosung Lee (AERA Open)
This study investigated whether and to what extent shared leadership in school was associated with a positive and equitable sense of school belonging among students from diverse backgrounds in the United States. We denoted shared leadership as collective practices that take place in schools in which principals enact inclusive practices in the decision-making process and teachers collaborate with their colleagues to support all students’ learning. We used linear mixed-effects modeling to analyze a nationally representative sample from the base-year data of the High School Longitudinal Study of 2009 (HSLS:09) provided by the National Center for Education Statistics (NCES). Our exploratory analyses revealed that shared leadership practices in school were positively associated with all students’ school belonging. We also found that shared leadership practices in school contributed to American Indian/Alaska Native students’ positive sense of school belonging through a cross-level interaction effect.